An offset surface to reduce radar cross section for airborne antenna out‐band. Issue 11 (9th August 2019) - Liu, Kuo; Wang, Lu; Dang, Tao; Wang, Mengjun; Zheng, Hongxing; Li, Erping
Abstract: To meet the needs of modern electronic warfare in better stealth performance of the weapon platform, we design an offset surface with metasurface structure, which greatly reduces the radar cross section for airborne antenna. The relation between surface unit size and attenuation frequency guides the design of offset surface that can work in the L‐band. The original strategy performed as cross‐array structure that plays well throughout the band at different angles, except 30° to 35°. An undesired reflection occurs at this angle gap. Therefore, we attempted to modify the structure as parallel‐array structure with same unit size. The results show that modification performs well at all angles in the passband, which meets the design requirements. We processed an offset surface sample and performed a joint test with an aircraft antenna to verify the superiority of the design.